Vacuum brazing of Mo to 316L stainless steel using BNi-2 paste and Cu interlayer. (May 2020) - Min, Mei; Mao, Yangwu; Deng, Quanrong; Wang, Geming; Wang, Shenggao
Abstract: Mo/316L stainless steel joints have been obtained by vacuum brazing using BNi-2 paste. Microstructural characterizations of joints reveal the favorable interfacial bonding. Two diffusion zones (DZ1 close to Mo and DZ2 close to 316L) are developed due to the inter-diffusions of base materials and BNi-2 filler. The DZ1 is mainly composed of Mo, MoNi and Cr-based solid solution (Cr (s, s)), while the DZ2 mainly consists of (Fe, Ni) solid solution, σ-FeCr and MoNi4 . The filler layer mainly contains Ni (s, s), Cr (s, s) and a small number of borides (Ni3 B and CrB). For the joint brazed with BNi-2 paste and Cu interlayer, a similar microstructure and phase formation are obtained at the Mo/filler layer and filler layer/316L interfaces, and partial dissolution of Cu foil in the molten fillers occurs during brazing. The microhardness distributions of the joints are correlated to the formed phases. The joints brazed with BNi-2 paste and Cu interlayer exhibit higher shear strength than those without Cu interlayer, suggesting that the residual stress can be partially alleviated by the Cu interlayer due to its superior plastic deformation ability. Furthermore, the thermal cycle tests reveal the excellent thermal shock resistances of the Mo/316L joints within the measured temperature range. Highlights: Mo/316L joints are obtained by vacuum brazing using BNi-2 paste and Cu interlayer. Two diffusion zones are developed due to inter-diffusions of base materials and BNi-2. Residual stress can be partially alleviated by plastic Cu interlayer. Joints exhibit excellent thermal shock resistance within measured temperature range.